Meningkatkan Kemampuan Komunikasi Matematis Dan Self Confidence Siswa Menggunakan Pendekatan PBL Berbantuan Geogebra - Andini, Dwi; Mulyani, Nenden; Wijaya, Tommy Tanu; Supriyati, Devi Nurul (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
This study aims to examine the mathematical communication skills of students whose learning using Problem Based Learning approach GeoGebra assisted compared with using ordinary learning. This research is using the experimental method. Population in this research is a student of class X SMAN 1 Parongpong West Bandung academic year 2017/2018 with a sample of research is a student of class X SMAN 1 Parongpong consisting of class X Mia 1 as control class and X Mia 4 as experiment class is taken at random. The instrument used in this research is a test of mathematical communication ability in the form of problem description as much as 8 questions, as well as Self Confidence scale. Data were analyzed using IBM SPSS Statistic 1.7 for windows program. From this research, the following results are obtained: (1) Improvement of mathematical communication ability of students whose mathematical learning using geographic assisted PBL approach is better than using ordinary learning. (2) Increased self-confidence of students using geographic-assisted PBL approach is better than students using conventional learning Keywords:       Communication Ability, Self Confidence, Problem Based Learning, Geogebra